Strategi Optimalisasi Fungsi Manajemen Dalam Pelaksanaan Pesantren Kilat Ramadhan - Sopwandin, Iwan (Universitas Islam Negeri Raden Intan Lampung, 2023)
Ramadan as a month of abundant rewards and forgiveness can also be used as a month of education (tarbiyah). Flash boarding schools, for example, can be one of these educational facilities. This study aims to gather information regarding the implementation of the management of the flash boarding school for Ramadan at the Baeturrohmah Ciroyom Tasikmalaya Mosque Prosperity Board (DKM). This study used a qualitative method with an action research approach. Data were analyzed through the stages of data condensation, data presentation, and conclusion. Meanwhile, to test the validity of the data, it was carried out with observation and triangulation. This research shows that the management functions used to optimize Islamic boarding schools in the mosque prosperity council (DKM) Baeturrohmah Ciroyom Tasikmalaya consist of: 1) Planning, the parties involved are representatives from various walks of life. Matters discussed in the planning include: a) the fixation of the implementation of the flash boarding school; b) the amount of costs to be allocated; c) the committee; and d) the teacher. 2) Implementation, consisting of the maturation of the concept (covering the determination of teaching materials and class divisions, determination of lesson schedules, determination of teachers, and preparation of budgets and sources of funds) and the implementation of flash boarding schools. 3) Supervision and evaluation, supervision activities are carried out by the mosque's prosperity council (DKM) and the implementing committee during the flash boarding school. While the evaluation is carried out by the implementing committee at the time after supervision and at the end of the patient's activities.